An overview of the taxonomy of Attalea (Arecaceae) - Pintaud, Jean-Christophe (2008)
The genus Attalea (Arecaceae) is distributed in continental habitats of the Neotropical region and in some Caribbean islands. Life forms of Attalea species vary from small acaulescent palms to tall and massive palms, always solitary. The ecological range of the genus encompasses most of the Neotropical ecosystems, from coastal sand dunes to sub-Andean forests up to 1600 m in elevation, lowland wet to dry forests, savannas, swamps, etc. The taxonomy of the genus has been poorly understood due to conflicting genus and species concepts that exist since the last decades. Taxonomical problems have been caused by the lack of adequate material, especially species of large size, loss of many types and difficulties in interpreting hybrids. In this article, I review the most recent taxonomic literature on Attalea. The number of species in Attalea varies from 29 to 67 depending on different authors, with a maximum estimate of 73 species when combining the revised publications. There is a consensus for the validity of 20 species among modern palm taxonomists. The most conflicting species or group of species are discussed in detail as well as the taxonomic significance of some characters such as the pattern of insertion of staminate flowers on rachillae, insertion of pinnae on rachis, and arrangement of fibrous strands in the endocarp.